Switzerland : Financial Sector Assessment Program; Technical Note-Regulation and Supervision of Asset Management Activities. (IMF Staff Country Reports; Country Report, 2019)
Financial Sector Assessment Program; Technical Note-Regulation and Supervision of Asset Management Activities.